Palliativversorgung von Menschen mit Demenz - Zieschang, Tania; Oster, Peter (Zeitschrift für Gerontologie und Geriatrie, 2012)
Patients with dementia are an important target group for palliative care since particularly in advanced stages and at the end of life they often have complex health care and psychosocial needs. However, people with dementia have inappropriate access to palliative care. So far, palliative care focuses on cancer patients. Among other reasons, this is due to the different illness trajectories: while in cancer a relatively clear terminal phase is typical, in dementia functional decline is gradual without a clear terminal phase, making advanced care planning more difficult. Good communication among health care providers and with the patient and his/her family is essential to avoid unnecessary or even harmful interventions at the end of life (e.g., inserting a percutaneous endoscopic gastrostomy, PEG). To maintain the patient’s autonomy and to deliver health care according to the individual preferences, it is important to appropriately inform the patient and the family at an early stage about the disease and problems that may occur. In this context, advanced directives can be helpful.
Gesehen am 16.08.2018